In Vitro Assessment of Antibacterial, Antioxidant, and Cytotoxic Activities of Essential Oil and Methanolic Extract of Satureja rechingeri Jamzad: Biological activities of Satureja rechingeri Jamzad - Amanzadeh, Yaghoub; Shokrzadeh, Mohammad; Banirazi Motlagh, Mohammad Reza; Bakhshi Jouybari, Hossein; Habibi, Ameneh; Modanloo, Mona; Habibi, Emran (Iranian Journal of Pharmaceutical Sciences, 2023)
Satureja rechingeri Jamzad is a highly aromatic species of Lamiaceae. This species is one of the rare and endemic plants of Iran. This study aimed to assess the biological properties such as the antibacterial, antioxidant, and cytotoxic activity of essential oil (EO) and methanolic extract of S. rechingeri collected from the west of Iran and analyzed the plant EO constituent. Gas chromatography/mass spectrometry (GC/MS) was performed for analyzing the EO. The antioxidant activities of extract from S. rechingeri were evaluated using DPPH radical scavenging assay. The major component of S. rechingeri EO was carvacrol (86.45%). The minimum inhibitory concentration value was 15.625 µl/ml for the bacterial strains. The extract exhibited antioxidant activity in DPPH radical scavenging assay (EC50 = 47.56 µg/mL). In addition, the total phenolic content in the plant methanolic extract was 79.9 mg/g gallic acid. The highest toxicity for essential oil was found in the MCF7 cell line with an IC50 value of 47.71 µg/ml. Carvacrol was the main component of S. rechingeri EO. The plant extract and EO showed considerable antioxidant and antimicrobial activity. It seems that this plant could be a commercial source of carvacrol.